ASSESSMENT OF THE DEVELOPMENT OF AN INTEGRATED WETLAND ECOSYSTEM E-MODULE OF STUDENTS' CRITICAL THINKING ABILITY AND ENVIRONMENTAL CARE ATTITUDE - Mardatilla, Mardatilla; Yustina, Yustina (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
This research aims to see the validity and practicality of the Wetland Ecosystem E-module which integrates students' critical thinking skills and environmental care attitudes. This type of research is research and development with the PLOMP development model. This research was carried out at the Biology Education Masters Program, FKIP, Riau University. The instruments used are validation questionnaire sheets by material experts, media experts and pedagogy experts, as well as practicality questionnaire sheets. The validity results show that overall the e-module that has been developed obtained an average score of 80.25% which is categorized as valid. The validation results for material experts were 78% in the valid category, 78.75% for media experts in the valid category, and 84% for pedagogical experts in the very valid category. Practicality was assessed based on three aspects, namely ease of use, time efficiency and benefits, with an average score of 93% obtained in the very practical category. The average score for the ease of use aspect was 97%, the time efficiency aspect was 93.46% and the benefits aspect was 96.05%. The conclusion of this research is that the Wetland Ecosystem E-module integrated with students' critical thinking skills and environmental care attitudes is declared valid and practical, so that it can be used as electronic teaching material in wetland ecosystem material in environmental science and disaster mitigation courses.